Uma proposta de instrumento para sistematização do processo de tomada de decisão em projetos do setor de arquitetura, engenharia e construção baseado na TRIZ - Regalla, Diana de Almeida Pinto (2018)
The increasing technological advances in Architecture, Engineering and Construction (AEC) industry are constantly influencing work processes and breaking paradigms, causing changes in the functional relations between the agents of this industry and intensifying the competitiveness between the architecture and engineering offices and between the builders. This fact evidences the need for design process organization, which can be achieved through systematic methodologies, since the lack of control of the creation process can result in ineffective methodological systems. The Inventive Problem Solving Theory (TRIZ) offers a systematic, human-oriented and knowledge-based approach, driving the creative problem-solving process. The proposal to use TRIZ in the initial stages of the process allows the delimitation of the search space for solutions in a systematic and efficient way. Its use comprises several techniques and consists essentially in the restructuring of a specific design problem in a generic problem whose solution has consolidated referential principles, Inventive Principles (IPs). The paper presents the adaptation of this classic theory, commonly used in the development of new products, for the AEC industry, a field not yet sufficiently explored by the theory, resulting in the proposal of an instrument to systematize the decision-making process in the face of contradictions. To test the instrument, a case study was conducted at the Martagão Gesteira Institute of Pediatrics and Child Care (IPPMG) of the Federal University of Rio de Janeiro (UFRJ). As a result, significant practical solutions for both validation of the instrument and the project itself have been achieved.